Reducing leaching losses of nitrogen and phosphorus in vegetable farms using a combination of biochar amendment and drip irrigation - LI Shixiong; HU Fei; PENG Yin; DABUXilatu; ZHANG Jun; LI Meicun (Guan'gai paishui xuebao, 2025)
【Objective】Nitrogen and phosphorus leaching from vegetable farms poses significant environmental risks and reduces agricultural profitability. Here, we present the results of an experimental study on the effectiveness of combining drip irrigation and biochar amendment in reducing nitrogen and phosphorus leaching in cabbage fields. 【Method】The field experiment was conducted with four treatments: ① conventional chemical fertilization (CK), ② soil amendment with 7 500 kg/hm2 of biochar combined with the conventional fertilization (B1), ③ drip irrigation with a 50% reduction of the fertilizer applied in CK (B2), and ④ combining B2 with 7 500 kg/hm2 of biochar amendment (B3). For each treatment, we measured the cabbage yield, nitrogen and phosphorus leaching losses, and changes in soil physicochemical properties.【Result】① Drip irrigation combined with biochar amendment and fertilizer reduction did not significantly reduce cabbage yield compared to CK. ② Compared to CK, B1 increased total nitrogen and phosphorus content in the soil by 12.29% and 10.21%, respectively, while reducing the concentrations of total nitrogen, nitrate nitrogen, and soluble phosphorus in leachate by 45.09%, 69.99%, and 39.45%, respectively. ③ B2 reduced the concentrations of total nitrogen, ammonium nitrogen, nitrate nitrogen, total phosphorus, and soluble phosphorus in leachate by 45.16%, 34.87%, 63.46%, 57.90%, and 55.04%, respectively, compared to CK. ④ B3, combining biochar amendment and fertilizer reduction under drip irrigation, reduced total nitrogen and phosphorus leaching by 46.66% and 48.57%, respectively, compared to CK. Principal component analysis indicated that fertilizer reduction was more effective in reducing nitrogen and phosphorus loss than biochar application, and their combination exhibited a synergistic effect.【Conclusion】The combination of biochar amendment with reduced fertilization under drip irrigation is highly effective in minimizing nitrogen and phosphorus leaching in vegetable fields, improving both environmental sustainability and agricultural profitability.